A Study of the Performance of the Local Exhaust Ventilation System at Welding Station using Computational Fluid Dynamics (CFD) Simulation - Yahya, Ahmad Redzuan; Zakaria, Hanis (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Local exhaust ventilation (LEV) system is an engineering control widely used in any welding workplace to control hazardous airborne contaminant exposure to an acceptable limit. Hence, this study is performed to analyse the performance of the LEV system by studying the air distribution using computational fluid dynamics (CFD) simulation. The components involved in this study are 14 capture hoods, 14 extraction arms and a ducting system. ANSYS 19.1 CFX software and two turbulence models which are k-ɛ and shear stress transport (SST), are used in this simulation study. The material assumption in this study is the air properties at 30°C considering the temperature of the LEV system where the welding stations operates in. The findings from the study show the velocity readings obtained by the simulation study are higher compare to the experimental study. By comparing the findings for each turbulent model with previous experimental results, it can be deduced that the k-ɛ and SST turbulence model of 0.05m element size can produce the minimum average percentage difference of 32.82 % and 33.82 % respectively. The percentage differences between the turbulence models and experimental study are notable when there is the 90° duct junction and sudden difference in the ducting diameter between ducting point 5 and 6. Therefore, a further decrease in the element size with a more refined mesh model needs to be dealt with to select the best element choice for the simulation study.